Organización contable en la misión Franciscana de zumba”, cantón Chinchipe, Período del 01 de octubre al 31 de diciembre del 2021. - Peñarreta Rodríguez, Mayra Alexandra (2022)
The Curriculum Integration work called: "ACCOUNTING ORGANIZATION IN THE "FRANCISCAN MISSION OF ZUMBA," CHINCHIPE CANTON, PERIOD FROM OCTOBER 01 TO DECEMBER 31, 2021" was carried out as a prior requirement to obtaining the title of Bachelor of Accounting and Auditing. This research work was developed according to the Academic Regime Regulations of the "Universidad Nacional de Loja," whose objective is to know the economic and financial situation of the organization. In addition, this work will serve as a source of support and information for future thesis work or as a reference tool in the field of accounting science. To comply with the first specific objective, the chart of accounts was drawn up, with its proper distribution and classification of the accounts based on the organization's needs. This process facilitated its management. Then the accounts manual was made where the concept, debit, credit, and balances of each of the accounts involved in the structure of the accounting system are detailed. For the development of the next objective, the auxiliary records of purchases and sales were prepared, allowing to detail in an orderly manner the transactions that are generated daily. In the same way, the accounts receivable assistant was carried out, the same one that helps us to have a greater control of the credits by the clients. Then, the accounts payable assistant was developed, which allows compliance with the obligations with the different suppliers. Finally, payment roles and monthly provisions were designed, while the respective depreciations are made. When carrying out the accounting process, the third and fourth objectives were met, which began with the physical verification of the stock of goods, values, rights, and obligations of the Zumba Franciscan Mission. After this, the Initial Inventory could be established, where its assets, liabilities, and equity is reflected, which is very useful for realizing the Initial Situation Statement. Next, the legal representative provided the necessary information to carry out the operations memorandum, continuing with registering transactions in the Daily Book. Then these were transferred to General Ledger, Trial Balance, and Work Sheet, where the adjustments corresponding to depreciation were made. Next, the preparation of the Income Statement, the Financial Position Statement, the Cash Flow Statement, and the Statement of Changes in Equity, with their respective explanatory notes, was concluded. 5 Finally, the conclusions and recommendations are presented, among which we can highlight in the Zumba Franciscan Mission from October 1 to December 31, 2021. It presents a loss for the year, which is reflected in the Income Statement. That is why it is recommended that the representative be able to make the best decisions regarding the loss of the registered financial year.